Solving a 3D Structural Puzzle - Hoeck, Casper Rønn (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book explores how nuclear magnetic resonance (NMR) spectroscopy may be used for spatial structural elucidation of novel compounds from fungal and synthetic sources. Readers will discover the exciting world of NOE (nuclear Overhauser effect), RDC (residual dipolar coupling) and J-coupling constants, both short- and long range. With emphasis on obtaining structural knowledge from these NMR observables, focus is moved from solving a static 3D structure to solving the structural space inhabited by small organic molecules. The book outlines the development and implementation of two Heteronuclear Multiple Bond Correlation-type NMR experiments, and the 3D structural elucidation of multiple known and novel compounds. In addition, a new method of back-calculating RDCs (allowing for more flexible structures to be investigated), and the synthesis and evaluation of novel chiral alignment media for ab initio determination of absolute stereochemistry of small molecules using RDCs are also included. Challenges that 3D structural generation of small compounds face are also covered in this work.